Easter Rioja, Joy of the People Readings from the Beatification of Bishop E. Angelelli and Fellow Martyrs - Taricco, Juan Matías (Teología, 2019)
The beatification of the Riojan martyrs, as a magisterial act, needs a process of recep- tion in the history and life of the communities. To achieve this reception it is necessary to incorporate various readings of the martyrial event and its meanings. This re-rea- ding process also requires validation and recognition criteria in order to generate narratives that are both historically and theologically legitímate and that allow an approximation to the testimony of the martyrs that is significant when walking the People of God in history and in the society. Criteria such as fidelity to the council, continuity and historical discontinuity of the subjects, presence of the Church in the world, among others and without claim of exclusivity, seek to help frame and raise various hermeneutics that enrich the provocation that God makes to his Church to Through the life of these witnesses.